2020
DOI: 10.1530/erc-19-0501
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E1 and cyclin E2 in ER+ breast cancer: prospects as biomarkers and therapeutic targets

Abstract: Cyclin E1 is one the most promising biomarkers in estrogen receptor positive (ER+) breast cancer for response to the new standard of care drug class, CDK4/6 inhibitors. Because of its strong predictive value, cyclin E1 expression may be used in the future to triage patients into potential responders and non-responders. Importantly, cyclin E1 is highly related to cyclin E2, and both cyclin E1 and cyclin E2 are estrogen target genes that can facilitate anti-estrogen resistance and can be highly expressed in brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 108 publications
(141 reference statements)
1
10
0
Order By: Relevance
“…CDK4 (75), cyclin E1 (76), and c-myc (77) play important parts in regulating G1-S transition. As G1-S transition overactivation occurs in the majority of malignant tumors, inhibitors of CDK4 and cyclin E1 have emerged as candidate drugs for tumor treatment (78,79). In our study, we showed that HNRNPC knockdown statistically inhibited CDK4, cyclin E1, and c-myc expression.…”
Section: Barbier Et Al Reported That H-ras Splice Variants Includingsupporting
confidence: 49%
“…CDK4 (75), cyclin E1 (76), and c-myc (77) play important parts in regulating G1-S transition. As G1-S transition overactivation occurs in the majority of malignant tumors, inhibitors of CDK4 and cyclin E1 have emerged as candidate drugs for tumor treatment (78,79). In our study, we showed that HNRNPC knockdown statistically inhibited CDK4, cyclin E1, and c-myc expression.…”
Section: Barbier Et Al Reported That H-ras Splice Variants Includingsupporting
confidence: 49%
“…The toxic effects of ARG on glioma cells (U87MG, T98G) via G1/S phase arrest ( Figure 3(a) ). Previous articles have shown that cyclin E was detected at the maximum level near the G1/S boundary [ 24 ] and that the correlation between the cyclin-dependent kinase 2 (CDK2) and the cell cycle was demonstrated [ 25 ]. Western blotting revealed that ARG significantly decreased the level of cyclin E and CDK2 (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is strongly consistent with previous reports that demonstrated the oncogenic function of Cyclin El in cancers. For instance, its oncogenic role was highlighted in breast cancer [26], ovarian cancer [27] and osteosarcoma [28]. More interestingly, Cyclin E1 could be mediated by G6PD overexpression and high Cyclin E1 expression predicted poor outcomes, which indicated that as a cell cycle-related molecular, Cyclin E1 might be a more crucial downstream target of G6PD in promoting ccRCC tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%